Quantitative Biology of Human Shelterin and Telomerase: Searching for the Weakest Point - Veverka, Pavel; Janovič, Tomáš; Hofr, Ctirad (International journal of molecular sciences, 2019)
The repetitive telomeric DNA at chromosome ends is protected from unwanted repair by telomere-associated proteins, which form the shelterin complex in mammals. Recent works have provided new insights into the mechanisms of how human shelterin assembles and recruits telomerase to telomeres. Inhibition of telomerase activity and telomerase recruitment to chromosome ends is a promising target for anticancer therapy. Here, we summarize results of quantitative assessments and newly emerged structural information along with the status of the most promising approaches to telomerase inhibition in cancer cells. We focus on the mechanism of shelterin assembly and the mechanisms of how shelterin affects telomerase recruitment to telomeres, addressing the conceptual dilemma of how shelterin allows telomerase action and regulates other essential processes. We evaluate how the identified critical interactions of telomerase and shelterin might be elucidated in future research of new anticancer strategies.
Keywords: shelterin; Protein Binding; telomerase; protein-DNA interaction; shelterinový komplex; inhibitory enzymů; Antineoplastic Agents; anticancer; assembly; telomere; Shelterin Complex; protein-protein interaction; protinádorové látky; zvířata; Humans; vazba proteinů; Telomere-Binding Proteins; telomerasa; Telomerase; quantitative biology; proteiny vázající telomery; Enzyme Inhibitors; lidé; inhibitor; Animals